2020
DOI: 10.1371/journal.pone.0244191
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diurnal variation on the performance of exhaustive continuous and alternated-intensity cycling exercises

Abstract: The purpose of this study was to explore the effect of time of day (TD) on two types of exercise protocols [continuous (CP) versus alternated (AP)]. Eleven physical education students (mean ± SD: age = 24.4 ± 1.2 years, aerobic peak power (APP) = 290 ± 31.9 W) underwent four sessions. These sessions were performed at 08:00 (AM) and 18:00 (PM) and consisted of cycling exercises until voluntary exhaustion at 90% APP (CP) or 70%-105% APP (AP) with the order of testing randomly assigned. Time to exhaustion (time l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Athletes' SJFT performances and physiological outputs did not differ at different times of the day. Similar findings were suggested by previous studies (Deschenes et al, 1998;Souissi et al, 2020). There are conflicting findings related to effect of time-of-day on RPE.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Athletes' SJFT performances and physiological outputs did not differ at different times of the day. Similar findings were suggested by previous studies (Deschenes et al, 1998;Souissi et al, 2020). There are conflicting findings related to effect of time-of-day on RPE.…”
supporting
confidence: 89%
“…In another study applied to soccer players, although peak anaerobic power was found higher in the afternoon compared to morning and evening, the changes in bLA was found similar (Ünver & Atan, 2021). It was stated that the different times of the day did not affect bLA before exercise but peak bLA was higher in the evening compared to morning in line with the increase in the exercise performance following the exhaustive exercises (Souissi et 2020). The effect of the time-of-day on the changes in exercise performance and bLA was not compatible.…”
mentioning
confidence: 92%
“…Exercise is performed at 23°C ± 0.1°C (60% ± 3% humidity). All conditions were performed indoors at the same time of the day (i.e., between 8:00 and 10:35) to minimize the effects of diurnal variations in the aerobic and anaerobic contributions to physical performance ( Dergaa, Varma, et al, 2021 ; Souissi et al, 2020 ). Figure 1 illustrates the study design.…”
Section: Population and Methodsmentioning
confidence: 99%
“…All tests were completed within two weeks, both before- and after- PT in thermoneutral condition [ 24 , 25 ] . All sessions were performed at the same time of the day to minimize the effects of diurnal variation in the measured parameters [ 26 ] . Fig 1 outlines the study protocol.…”
Section: Methodsmentioning
confidence: 99%